PENGARUH PROGRAM PEMUTIHAN PAJAK KENDARAAN BERMOTOR, PEMBEBASAN BEA BALIK NAMA KENDARAAN BERMOTOR, DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Januar Sonya Maulani Kusasih; Nanik Kustiningsih (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to determine how the effect of the whitening program, name change reactions, and socialization on motor vehicle tax payers (a case study at the West Surabaya Samsat Joint Office). The type of research used in this study is quantitative research using Multiple Linear Regression Analysis and processed using the IBM SPSS Version 26 program. The results of this study state that: (1) Variable (X1) PKB Whitening Program has a significant effect, and also Variable (X1 ). ) is able to affect the Variable (Y); (2) Variable (X2) Liberation of BBNKB does not have a significant effect, and also variable (X2) does not affect variable (Y); (3) Variable (X3) Socialization of Taxation has a significant influence, and also Variable (X3) is able to influence Variable (Y); (4) The findings of Hypothesis 4 test indicate that the Bleaching Program, Tax Socialization, all have an impact on taxpayer compliance simultaneously